If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -13 = 11x + -2 Reorder the terms: -13 + 14x = 11x + -2 Reorder the terms: -13 + 14x = -2 + 11x Solving -13 + 14x = -2 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -13 + 14x + -11x = -2 + 11x + -11x Combine like terms: 14x + -11x = 3x -13 + 3x = -2 + 11x + -11x Combine like terms: 11x + -11x = 0 -13 + 3x = -2 + 0 -13 + 3x = -2 Add '13' to each side of the equation. -13 + 13 + 3x = -2 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = -2 + 13 3x = -2 + 13 Combine like terms: -2 + 13 = 11 3x = 11 Divide each side by '3'. x = 3.666666667 Simplifying x = 3.666666667
| 3x+3-6x+6-9x-9=12-12x+15x+18+27 | | 5/6*-1/5x+4=7/10x | | 5x-41=3x-11 | | 0=-6x-4x+5 | | .8x+.5y=6597 | | (x+5)(x-5)-x(x-1)=0 | | 10x-5x-6-10x=7 | | 3(z+9)-(6z-9)=-4z | | 10/3-5=4/3x+7 | | 8+6x-4=9x+12-7x | | 7z-7=8z | | 25+17s=76 | | x/16=-8 | | -7-3=4x+7-3x | | x/25=-20+20 | | x-12=-29 | | 8-.5Q=1Q | | 8s=-72 | | 56*23-67/98*32= | | 7202-.23Q=.46Q | | 375-.25Q=.5Q | | 5.6q-5.3-5.2q=-0.6q-1.2 | | 9x-18+36/9x | | 24-0.10Q=.20Q | | 8x-6y=-96 | | x-8=-1+3 | | 5x+67=10x-13 | | 3x-12/x-2a+4/9 | | 12x+8-5=11x-2 | | 3y+2x=10 | | 3(y+2)+y=u(y-1)+10 | | 4g=-5s |